Neural Controls of Prostaglandin 2 Pyrogenic, Tachycardic, and Anorexic Actions Are Anatomically Distributed - Skibicka, Karolina P. (Endocrine Society, 2011)
Fever and anorexia are induced by immune system challenges. Because these responses are adaptive when short lasting but deleterious when prolonged, an understanding of the mediating neural circuitry is important. Prostaglandins (PGE) are a critical signaling element for these immune responses. Despite the widespread distribution of PGE receptors throughout the brain, research focuses on the hypothalamic preoptic area as the mediating site of PGE action. Paraventricular nucleus of the hypothalamus (PVH), parabrachial nucleus (PBN), and nucleus tractus solitarius (NTS) neurons also express PGE receptors and are activated during systemic pathogen infection. A role for these neurons in PGE-induced fever, tachycardia, and anorexia is unexplored and is the subject of this report. A range of PGE(2) doses was microinjected into third or fourth ventricles (v), or directly into the dorsal PVH, lateral PBN, and medial NTS, and core and brown adipose tissue temperature, heart rate, locomotor activity, and food intake were measured in awake, behaving rats. PGE(2) delivery to multiple brain sites (third or fourth v, PVH, or PBN) induced a short- latency (<10 min) fever and tachycardia. By contrast, an anorexic effect was observed only in response to third v and PVH stimulation. NTS PGE(2) stimulation was without effect; locomotor activity was not affected for any of the sites. The data are consistent with a view of PGE(2)-induced effects as mediated by anatomically distributed sites rather than a single center. The data also underscore a potential anatomical dissociation of the neural pathways mediating pyrogenic and anorexic effects of PGE(2).